Chemical and structural properties of dissolved black carbon released from biochars. (January 2016) - Qu, Xiaolei; Fu, Heyun; Mao, Jingdong; Ran, Yong; Zhang, Dainan; Zhu, Dongqiang
Abstract: Black carbon (BC) has drawn wide interest due to its important role in the global carbon budget and pollutant sequestration. Its soluble carbonaceous component, dissolved BC, is the key for understanding many geological and environmental processes of BC. In this study, we show that dissolved BC can be readily released in water under stirring from bulk BC produced by the slow pyrolysis of biomass. The chemical and structural properties of bulk, colloidal, and dissolved BC were thoroughly examined using elemental analysis and a variety of spectroscopic techniques. Compared with bulk BC, dissolved BC contained 30–40% more oxygen and more polar functional groups, but lower aromaticity and less condensed aromatic clusters. It is concluded that dissolved BC consists primarily of small aromatic clusters substituted by carboxylic groups, and by phenolic groups to a less extent. Dissolved BC represents an important source for soil and aquatic natural organic matter. The structure of dissolved BC was compared with some well-characterized humic substances. Results obtained from this work would shed new light on the mobility, liability, and reactivity of BC, as well as its impact on the global carbon budget and contaminant transport.